Rice Fields Chemical and Physical Properties and the Implications on Breeding Strategie - Souleymane, O.; Nartey, E.; Joseph, B.T.B.; Manneh, B.; Ofori, K.; Danquah, E. (2018)
Soil related constraints are major limiting factors in crop production in the Sahel. The objective of this study was to assess the properties of farmer's fields soil and irrigation water in Niger and the implications in rice improvement. Composite soil samples were collected from irrigated and non-irrigated fields. Sample of irrigation water was also collected. Physical and chemical analyses were performed in the laboratory. The results showed that most of rice fields were clayey and the non irrigated ones were mostly sandy. The soils were acidic and saline, the electrical conductivity ranged from 2.2 to 16.5 decisiemens per meter. The T-test showed that total dissolved salt, sodium adsorption ratio, cation exchange capacity, and organic matter percentage were significantly higher in irrigated fields than non-irrigated fields. The irrigated soils pH varied from 3.2 to 6.8, the electrical conductivity was greater than 4, and the sodium adsorption ratio was below 13 while the exchangeable sodium percentage was below 15. The irrigation water samples varied in term of ion content from site to site. The total sodium quantity estimated to be deposited varied from 87 kg/ha/year to 218 kg/ha/year. Rice fields' soils are saline and are getting worsened by irrigation water that contains salt. Therefore, the development of rice varieties that could withstand osmotic and ionic salt stress is necessary for sustainable production in the Sahel ecozone.